PENGELOLAAN ARSIP DI KANTOR BADAN PENGENDALIAN DAMPAK LINGKUNGAN DAERAH KOTA PADANG - DESI PUTRI (Universitas Negeri Padang, 2018)
The fact in the field suggests that the archives conducted by the employees in a state that has not been ideal. This study aimed to obtain information of archives management in the environmental impact control agency office area of the town padang, in the procedure site there is archives, save, and Extermination management archives. This research is descriptive. Population in this research is the employee that there is in the environmental impact control agency office area of the town padang. who is totaled 19 people. Because of the less population of member the writer using the population research. Data collection tool was a questionnaire with Likert scale model that has been tested for validity and reliability. Overall average scores in the environmental impact control agency office area of the town padang is 3.50. It can be concluded that the archives managemen environmental impact control agency office area of the town padang is had been quite right.Keyword: Archives Management